Critical success factors for the implementation of problem solving principles of lean in Malaysian automotive industry - Touhidul Islam, A.S.M. (2020)
Lean has become the most popular management system as it provides tremendous benefits in an easier way. Although there are abundant literatures on lean, study in deeper details which is specific to problem solving of lean is limited. This study is intended to explore standard elements of principles of problem solving in lean with emphasize on their importance to get more reliable results. This element wise analysis is an added approach to the methodology. After compiling and grading 36 success factors, a case study has been conducted to rank the factors by a focus group of 16 lean sigma experts in a Malaysian Automotive industry. Then Decision Making Trial and Laboratory method is used to compare pair wise impact relations to find out critical success factors. Applying this method for both overall and element wise analysis has provided important insights about 17 critical factors. In short, the author interprets the results that when there is a compelling need to build a lean problem solving culture in an organization, top management needs to link metrics of performance and accountability of employees to business strategy; and create quality awareness and manage continuous improvement and learning with detailed plan properly by empowering and motivating process owners in production and other departments including suppliers to understand the process, communicate effectively and work as a team provided right kind of training for new knowledge and mindset to apply the full set of principles and tools. Finally, a conceptual framework of critical success factors has been built as per association with specific elements of principles. For the industrial practitioners of lean, these results along with thoughtful discussions will guide to establish problem solving principles of lean effectively. This study also directs to explore ways to establish other principles as well. The author assumes that this research may take complete lean implementation to the next level of success.